Developing stromal instructive niches to promote wound healing - Latif, Arsalan (2021)
Wound healing is a complex biological process involving various cell types across spatial and temporal phases. Dysregulation in any of these phases, such as in the case of diabetic wounds, burn injuries or implantation of medical devices may result in non-healing wounds, chronic wounds, and/or fibrosis. The accelerated formation of granulation tissue has been studied to promote and accelerate wound healing. Fibroblasts are the prevalent cell type of the granulation tissue and have been shown to play an important role in both healing processes and fibrosis, governed by the nature of biochemical stimuli, e.g., from immune cells such as macrophages, and the physicochemical characteristics of the microenvironment and/or implanted biomaterials. Biomaterial surface chemistry is known to influence phenotype and functions of various cell types including fibroblasts. Hence, the overall aim of this study was to discover new polymer chemistries that regulate/modulate fibroblast behaviour and phenotype, thereby governing the outcome of wound healing.